Copyright Dispute in the Digital Era Between PT Oyo Rooms Indonesia (OYO) and PT Duit Orang Tua - R.Rahaditya; Aldizya Jasmine Harum Antika (Universitas Semarang, 2025)
This study aims to examine the legal aspects of copyright infringement in the digital context, particularly under Law Number 28 of 2014 on Copyright, and analyze its implications for companies that utilize digital content without authorization. The urgency of this research stems from the increasing prevalence of unauthorized use of protected content, particularly in the hospitality sector, where visual media play a central role in marketing strategies. The study employs a normative juridical approach by analyzing relevant legislation and actual court decisions, focusing on the copyright dispute between PT OYO Rooms Indonesia (OYO) and PT Duit Orang Tua (DOT). In this case, OYO allegedly used and modified DOT's photos without permission for commercial promotion purposes on various online platforms. The court found OYO guilty of copyright infringement in decision Number 45/Pdt.Sus-HKI/Hak Cipta/2020/PN Jkt.Pst, and this decision was upheld by the Supreme Court in cassation Number 649 K/Pdt.Sus-HKI/2021. The research highlights that the Indonesian legal framework has been able to provide effective protection to legitimate copyright holders. The novelty of this study lies in its doctrinal analysis of a real-world judicial decision, offering insights beyond the theoretical approaches in previous literature. The study concludes that Indonesia's copyright regime has proven effective in this case and finds that corporate responsibility and due diligence are key in preventing infringement. The study recommends that digital platforms and business actors strengthen their internal compliance systems to mitigate legal risks and promote responsible content usage.